2010
DOI: 10.1037/a0017166
|View full text |Cite
|
Sign up to set email alerts
|

Role of task-directed attention in nonconscious and conscious response priming by form and color.

Abstract: Prior research on visual priming suggests that during nonconscious processing attention can be directed to single stimulus dimensions such as form or color. In the current experiment, nonconscious priming was compared to conscious priming by employing masking techniques that render primes invisible (masked) or visible (unmasked) to the observers. Observers were asked to respond to the form, the color, or the combination of form and color of the mask-probe that followed either a masked or an unmasked prime. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
43
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 62 publications
8
43
1
Order By: Relevance
“…Such an extended model of evidence accumulation and decay could account for priming effects like the current ones. Moreover, priming effects are known to depend on allocation of feature-based and space-based attention (Tapia, Breitmeyer, Jacob, & Broyles, in press;Tapia et al, 2010). Besides incorporating similar attentional components, explanations of the comparison effects would require additional processes, including those supporting (1) active maintenance of the encoded prime information in VWM and (2) comparison of the prime information available at any given SOA to the encoded probe information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an extended model of evidence accumulation and decay could account for priming effects like the current ones. Moreover, priming effects are known to depend on allocation of feature-based and space-based attention (Tapia, Breitmeyer, Jacob, & Broyles, in press;Tapia et al, 2010). Besides incorporating similar attentional components, explanations of the comparison effects would require additional processes, including those supporting (1) active maintenance of the encoded prime information in VWM and (2) comparison of the prime information available at any given SOA to the encoded probe information.…”
Section: Discussionmentioning
confidence: 99%
“…We followed methods previously detailed in Tapia, Breitmeyer, and Schooner (2010). Priming and comparison tasks were performed in a semi-lit room.…”
Section: Apparatus and Stimulimentioning
confidence: 99%
“…Importantly, it was found that implicit learning on the background color sequence occurred during the learning process of alphabet sequence. Some researchers argued that attention would be guided by the relevance of non-target information (Endo &Takeda, 2004), both on conscious and on unconscious level (Tapia, 2010). In the present study, participants were able to implicitly processing the background color sequence even when the sequence was set as random, which may suggest that unconscious attention tends to be casted on the whole learning environment rather than on limited information.…”
Section: Discussionmentioning
confidence: 51%
“…Second, a number of studies on visually normal observers have shown that stimuli that are rendered invisible by a visual mask can nonetheless guide the deployment of space-based attention (Ansorge & Heumann, 2006;Ansorge, Heumann, & Scharlau, 2002;Scharlau & Ansorge, 2003;Skalska, Jaśkowski, & van der Lubbe, 2006). And third, it turns out that a variety of masked, and thus unconsciously processed, object features can be selectively attended (Bahrami, Carmel, Walsh, Rees, & Lavie, 2008;Finkbeiner & Palermo, 2009;Kiefer, 2012;Kiefer & Brendel, 2006;Kiefer & Martens, 2010;Martens, Ansorge, & Kiefer, 2011;Schmidt & Schmidt, 2010;Shin, Stolte, & Chong, 2009;Tapia, Breitmeyer, & Schooner, 2010). Hence, attention is confined neither in its deployment nor in its effects to conscious processing of stimuli.…”
Section: Visual Attention In Relation To the Visual Unconscious And Cmentioning
confidence: 99%